Experimental characterization of fatigue life of ZrB2-SiC based ultra high-temperature ceramic matrix composites. (March 2023) - Reimer, T.; Di Martino, G.D.; Sciti, D.; Zoli, L.; Galizia, P.; Vinci, A.; Lagos, M.A.; Azurmendi, N.
Graphical abstract: Highlights: UHTCMC with ZrB2 -SiC matrix and either short or long carbon fibers are investigated. The objective is the experimental characterization of the UHTCMCs fatigue life. Two methodologies are employed: random vibration and sine resonance track and dwell. Finite element analyses allow to reconstruct the stress distribution during tests. Stress-fatigue life curves are obtained for the two class of materials. Abstract: The development process of new Ultra High-Temperature Ceramic Matrix Composites (UHTCMC) for use in severe environments typical of space applications, such as thermal protection or rocket components, still lacks useful data for what concerns the properties influencing the structural behavior under the different load conditions. In particular, the fatigue life of the material plays a fundamental role in the design of full systems determining their resistance to typical vibrational loads. However, this property has been rarely investigated for UHTCMCs and its experimental characterization presents uncertainties related to the material specific behavior, which does not allow the application of traditional methodology employed for isotropic materials. In the present work, two different methodologies are proposed and applied to new ZrB2 -SiC-based UHTCMCs, with either short or long continuous fibers, yielding in combination with numerical analyses to the determination of the σ/N curve for the two classes of materials.